Agency and institutional influences on franchising decisions - Barthélemy, Jérôme (Journal of Business Venturing, 2011)
While the franchising literature has typically relied on agency theory, efficiency considerations may not fully explain decisions to expand through franchising or company ownership. In this study, I re-examine franchising decisions using insights from institutional theory. The key tenet of institutional theory is that decisions are influenced by isomorphic pressures arising from the environment. Economic rationales such as the achievement of efficiency are thought of as less pervasive concerns. I begin by investigating whether institutional theory explains variance in franchising decisions beyond what is explained by agency theory. Then, I explore the extent to which institutional considerations moderate the relationships between agency considerations and franchising decisions. Hypotheses are tested on a unique database of 132 French franchise chains. Empirical results suggest that successful competitors' use of franchising explains variance in the focal chain's use of franchising beyond what is explained by the importance of local managerial inputs and the threat of franchisee opportunism. In addition, the threat of franchise opportunism is less strongly related to the focal chain's use of franchising when successful competitors have a high proportion of franchised outlets. Overall, findings from this study suggest that researchers should supplement agency theory with institutional theory to adequately explain franchising decisions.